S79 COPD exacerbations in routine clinical practice during COVID-19 in England in 2020. (11th November 2022) - Rothnie, KJ; Tritton, T; Han, X; Holbrook, T; Numbere, B; Ford, AF; Massey, L; Fu, Q; Hutchinson, FM; Birch, HJ; Leather, D; Sharma, R; et al.
Abstract : Introduction/Objectives: During the UK COVID-19 pandemic, patients with severe chronic obstructive pulmonary disease (COPD) were considered 'clinically extremely vulnerable' and were instructed to reduce social contact to only essential contact (termed 'shielding') for periods of high coronavirus prevalence. There is limited evidence of the impact of COVID-19 on the burden associated with patients with respiratory diseases. This study describes the changes over time in COPD exacerbation frequency stratified by disease severity. Methods: This was a retrospective dynamic cohort study of English COPD patients (FEV1 /FVC <0.7) aged ≥35 years, for the period from Mar 2018 until Aug 2020 using the Clinical Practice Research Datalink Aurum linked to Hospital Episode Statistics datasets. Monthly proportions of patients to experience a moderate or severe COPD exacerbation were described by GOLD 2019 disease grade. Results: In total, 119, 512 incident and prevalent COPD patients (mean [SD] age: 69.6 [10.6] years, 54.1% males) were included; 41.0%, 27.1%, 4.6%, 7.1% and 20.2% of patients were classified as GOLD A, GOLD B, GOLD C, and GOLD D disease grade groups and the unclassifiable group, respectively, in the 12-month baseline period. Severe exacerbations over time, stratified by GOLD grade at baseline, are shown in figure 1 . The proportion of patients with COPD experiencing a moderate exacerbation in January 2020 (stratified by GOLD grade at baseline) was 3.33% (GOLD A), 4.62% (GOLD B), 8.01% (GOLD C) and 8.82% (GOLD D); these proportions decreased to 1.04% (GOLD A), 1.90% (GOLD B), 3.65% (GOLD C) and 4.71% (GOLD D) by April 2020. Conclusion: Among patients with COPD in routine clinical practice in England, the frequency of moderate and severe exacerbations declined between January 2020 and April 2020 for most stratification groups and remained low through to August 2020. When comparing GOLD grade at baseline, the proportion of patients to experience an exacerbation increased with increasing disease severity grade. Please refer to page A211 for declarations of interest related to this abstract.